Understanding needs and expectations to start effective communities of practice - Sanne H. Elbrink; Shandell L. Elmer; Richard H. Osborne (BMC, 2023)
Abstract Background Communities of practice (CoPs) are frequently used in health settings to enhance knowledge and support action around public health issues. Yet, most are ineffective and often at risk of not delivering on this promise. To prevent loss of time and resources by organisations, facilitators, and members, this paper argues for a reliable assessment of the needs of people who intend to join and to set realistic expectations to assure effective communities of practice. This research proposes a valid and reliable needs assessment and analysis tool for starting communities of practice, by presenting the results of using such a tool. Methods Inception needs assessments were developed, tested and administered to 246 respondents entering five communities of practice that focused on one of three public health issues: health literacy, mental health literacy and trauma-informed care. One community of practice had a global audience, four were based in Australia. Data from the needs assessments were analysed qualitatively and supplemented with descriptive statistics. Results were used to develop an analysis tool to support future communities of practice. Results The short-term expectations of respondents included seeking to increase their knowledge and getting to know other members of the community of practice. Long-term expectations shifted towards undertaking action, collaborating and improving health outcomes. While respondents learning expectations included a wide range of topics, they articulated very specific knowledge they expected to share with others. There were high expectations of receiving practical support from the facilitator and a strong preference for meetings with synchronous interaction. Most respondents who planned to join focused initially on the direct and individual benefits and participation they expected from others, whereas they indicated limited intention to actively contribute to the learning needs of other community members. Respondents appeared to need to take time to build self-confidence and trust, and frequently applied a wait-and-see attitude. Conclusions The findings of this study suggest that an inception needs assessment allows members to express their needs and expectations, which directly informs the direction and structure of a community of practice, gives voice to members, and supports facilitators in managing expectations.